Immigrant women’s experiences of maternity services in Canada: a meta-ethnography - Higginbottom, Gina M.A.; Hadziabdic, Emina; Yohani, Sophie; Paton, Patricia (Elsevier, 2014)
Objective: to synthesise data on immigrant women's experiences of maternity services in Canada. Design: a qualitative systematic literature review using a meta-ethnographic approach. Methods: a comprehensive search strategy of multiple databases was employed in consultation with an information librarian, to identify qualitative research studies published in English or French between 1990 and December 2011 on maternity care experiences of immigrant women in Canada. A modified version of Noblit and Hare's meta-ethnographic theoretical approach was undertaken to develop an inductive and interpretive form of knowledge synthesis. The seven-phase process involved comparative textual analysis of published qualitative studies, including the translation of key concepts and meanings from one study to another to derive second and third-order concepts encompassing more than that offered by any individual study. ATLAS.ti qualitative data analysis software was used to store and manage the studies and synthesise their findings. Findings: the literature search identified 393 papers, of which 22 met the inclusion criteria and were synthesised. The literature contained seven key concepts related to maternity service experiences including social (professional and informal) support, communication, socio-economic barriers, organisational environment, knowledge about maternity services and health care, cultural beliefs and practices, and different expectations between health care staff and immigrant women. Three second-order interpretations served as the foundation for two third-order interpretations. Societal positioning of immigrant women resulted in difficulties receiving high quality maternity health care. Maternity services were an experience in which cultural knowledge and beliefs, and religious and traditional preferences were highly relevant as well but often overlooked in Canadian maternity settings. Key conclusions and implications for practice: in order to implement woman-centred care, to enhance access to maternity services, and to promote immigrant women's health, it is important to consider these women's social position, cultural knowledge and beliefs, and traditional customs in the health care.